Performance improvement based on a novel 240∘ clamped space vector PWM with constant DC link voltage for single-stage EV powertrains - Syed Jahania Shah; Hafsa Qamar (Results in Engineering)
Modern electric vehicle powertrains integrate a high voltage battery that connects directly to the traction inverter, eliminating the need for a DC-DC stage. 240∘-clamped space vector PWM (240CPWM) is a low-loss pulse width modulation (PWM) technique that reduces switching losses by over seven times at unity power factor compared to conventional space vector PWM (CSVPWM). 240CPWM has been studied in a two-stage architecture, consisting of a DC-DC converter followed by a DC-AC inverter where the DC-DC converter controls the dynamically varying DC link voltage required for 240CPWM. However, two-stage configuration leads to a higher number of switching devices and hence results in high switching and conduction losses as compared to single-stage architecture. The advantages of 240CPWM can be fully maximized in terms of reducing the switching losses when its performance is evaluated in a single-stage architecture. However, the performance of 240CPWM in a single-stage architecture with constant DC link voltage has not been studied before. This work explores the application of 240CPWM in a single-stage architecture, eliminating the DC-DC stage and maintaining a constant DC link voltage for the first time. A key challenge of 240CPWM without the DC-DC stage is its reliance on maximum modulation index, which limits adaptability to varying motor speeds. This paper discusses a control method to drive the EV powertrain at varying speeds. The theoretical concepts are validated with an 8 kW hardware prototype. The proposed 240CPWM with constant DC link voltage achieves a full-load efficiency of around 98%, compared to 96% with conventional methods.